Immediate randomized use of platelet-rich plasma after fractionated CO2 laser in high skin photo type: Uso inmediato del plasma rico en plaquetas post laser CO2 fraccionado en fototipo de piel alto - Saco-Mera, Edmundo (2019)
Introduction: The treatment with carbon dioxide (CO2) laser fractionated in high skin phototypes, can result in pigmentation disorders, persistent erythema, edema, appearance of acne outbreak, among others. Due to this, it is necessary to apply complementary techniques that minimize these adverse effects. Objective: To identify the safety, efficacy and satisfactory synergistic effects after the application of platelet-rich plasma (PRP) after application of fractionated CO2 laser in the face with high phototypes, in order to diminish the adverse effects. Method: Clinical experimental study - open clinical trial - randomized with a universe of 32 hemies with phototypes IV and V of Fitzpatrick. A fractionated CO2 (CO2RE-Syneron Candela) laser was used and immediately autologous PRP was applied in the case hemifields. In controls, betamethasone and petrolatum. The photographic results were compared by showing them to 3 expert doctors without previous information so that they could determine the short, medium and long term findings in a simple scale. This was done at the skin clinic between July 2017 and September 2018 in Lima - Peru. Result: In the short term, satisfactory results were observed in the hemies treated with PRP. There was a decrease in the presence of post-inflammatory hyperpigmentation, erythema, edema and the appearance of acne, as well as an increase in the effect of facial tightening, attenuation of naso-genital grooves and expression lines in the hemias treated with PRP. However, in the long term, these last improvements are not significant in relation to the other control midfaces. Discussion: The fractionated CO2 laser generates histopathological changes similar to the wounds, so that the PRP absorbed at transepidermic level accelerates healing and reduces the possibility of side effects. Important results are seen in the prevention of dyschromias in these phototypes. Laser therapy combined with PRP is associated with greater satisfaction with laser monotherapy. The expected results are in early stages of recovery, while in the long term, there are no significant differences between the two midfaces. Conclusion: These results, in our population of high phototype, suggest that the immediate use of PRP post laser fractionated Co2, is an effective method to improve rehabilitation and healing, reducing the patient's downtime and decreasing the risks of adverse effects - secondary, It should be considered as an effective therapeutic alternative as post laser treatment. The small series of cases presented, leaves open the door to work with greater population and it would be very useful to be able to contrast the results obtained with those of future authors.